Pendampingan Lesson Study untuk Menciptakan Learning Community bagi Guru Matematika di SMP Muhammadiyah Kabupaten Bantul - Dwi Astuti; Harina Fitriyani (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2018)
Increasing the professionalism of an educator is important. One effort that can be done to improve professionalism is the collaboration between educators. Lesson study is an activity that can facilitate educators to observe each other's learning processes. Training activities and mentoring learning studies are carried out to create a learning community for mathematics teachers. The target of this activity is the Muhammadiyah Junior High School / MTs math teacher in Bantul Regency. The target of this service activity is the educator of learning problems that can be learned in learning activities. The practice of lesson study can be done at the level of the Subject Teacher Training (MGMP). Two activities in training activities which included lecture and discussion activities, as well as mentoring activities that contained lesson lessons. This activity is successful and can provide experience for participants